Contributing to the knowledge of Pantanal Flora: a new endemic species of Dimerostemma (Asteraceae: Heliantheae) from Mato Grosso do Sul, Brazil - Mendes, Daniel De Menezes; Welker, Cassiano A. Dorneles; Farinaccio, Maria Ana; Teles, Aristônio Magalhães (Phytotaxa, 2024)
Dimerostemma pantanalense is a new species, which is described, illustrated, and discussed in this paper. The species can only be found in the municipalities of Ladário and Corumbá, Mato Grosso do Sul state, Pantanal, Brazil. It is preliminarily categorized as Critically Endangered (CR) due to the advance of urbanization and the risk of fires in the Pantanal. It is morphologically similar to D. annuum but differs by its life-cycle perennial (vs. annual), leaves opposite and alternate (vs. only opposite), sessile (vs. subsessile with petiole up to 5 mm long), lanceolate (vs. linear), venation suprabasal acrodromous imperfect (vs. hyphodromous), adaxial and abaxial leaf surfaces strongly villous to estrigose and glandular (vs. only nearly glabrous), receptacle convex to conical (vs. only convex), phyllaries 3-seriate (vs. 2-seriate), conduplicate palea carinate-alate (vs. not carinate-alate), cypselae oblanceolate to obovate (vs. subquadrangular) and pappus coroniform with two slightly developed awns (vs. coroniform with two well-developed awns). We present photographs and line drawings of the new species, along with discussions on its geographical distribution, habitat, phenology, and conservation status. Additionally, we provide an identification key for species of the genus in the Brazilian Pantanal.